Working capital management through the business cycle: Evidence from the corporate sector in Poland - Paweł Mielcarz; Dmytro Osiichuk; Paweł Wnuczak (Contemporary Economics, 2018)
The paper examines the influence of the business cycle on working capital management strategies based on evidence from the Polish corporate sector. By exploring the interrelation between working capital investment and profitability ratios, we attempt to define the respective transmission mechanisms and summarize the principles of sound financial management across the economic cycle. We found that more profitable companies tend to implement a more conservative working capital management strategy during recessions and that underperforming firms may be urged to cut working capital in response to plummeting cash flows. The accumulation of precautionary cash reserves appears to help firms navigate through times of economic turmoil. The paper highlights the importance of working capital management for optimizing a firm's profitability. Research outcomes may point to the redistributive function of trade finance under conditions of financing constraints, which become particularly acute during troughs aggravated by a credit market crunch.
Keywords: G32; 330; working capital; business cycle; profitability